Guillain-Barré Syndrome in Patient With SARS-CoV-2 PCR Positivity Treated Successfully With Therapeutic Exchange Plasma: A First Case Report From Vietnam - Duong-Quy, Sy; Huynh-Truong-Anh, Duc; Nguyen-Thi-Kim, Thanh; Nguyen-Quang, Tien; Nguyen-Chi, Thanh; Tran-Xuan, Quynh; Nguyen-Nhu, Vinh; Ngo, Carine; Craig, Timothy (Frontiers in Neurology, 2022)
Since the first case of GBS-associated SARS-CoV-2 (Covid-19) infection reported in 2020, a series of cases have been published in some countries. In this case report, we present a young patient with GBS, whose clinical and laboratory data were appropriate for the diagnosis of GBS due to COVID-19 infection. Neurological examination revealed the muscular weakness of lower limbs with Medical Research Council (MRC) scale of 2/5 associated with diminished reflexes. Laboratory studies showed the positive nasal swab RT-PCR test for Covid-19, leukopenia, increased ferritin and LDH levels, normal electrolyte and liver and kidney function, and normal chest X-ray. The result of cerebrospinal fluid showed the albuminocytologic dissociation. The patient was treated with remdesivir, dexamethasone, anticoagulation, and therapeutic plasma exchange (TPE). Patient’s muscle weakness was significantly improved after one week of admission. He was discharged at 23th days of hospitalization and followed-up in the out-patients department.